2019
DOI: 10.3390/ijerph16122219
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory of Smoking and Incidence of Atherosclerotic Cardiovascular Disease among Korean Young Adult Men

Abstract: Introduction: Smoking among young adults is associated with atherosclerotic cardiovascular disease (ASCVD) in middle age. Our aim was to analyze the trajectory of smoking in young adults and analyze the effects of the trajectory group on incident ASCVD. Methods: This study was conducted among 60,709 young adult men aged 20–29 years who received health screening every two years from 1992–2004. Trajectory analysis was performed through smoking survey data measured 7 times during this period. ASCVD, including isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In addition, the difference originated from the participants. The sample in our study was larger, and we included all adult men aged ≥20 years for the analysis, whereas the studies of Jee et al 15 , 18 only recruited young individuals aged 20–39 years or 20–29 years.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the difference originated from the participants. The sample in our study was larger, and we included all adult men aged ≥20 years for the analysis, whereas the studies of Jee et al 15 , 18 only recruited young individuals aged 20–39 years or 20–29 years.…”
Section: Discussionmentioning
confidence: 99%
“…Even-numbered and odd-year births have been provided health examination by National Health Insurance Service (NHIS). The characteristics of this study can be found in the previously reported Korean Cancer Prevention Study (KCPS) [ 14 , 15 ]…”
Section: Methodsmentioning
confidence: 99%
“…Even-numbered and odd-year births have been provided health examination by National Health Insurance Service (NHIS). The characteristics of this study can be found in the previously reported Korean Cancer Prevention Study (KCPS) [14,15] For this study, 430,951 individuals (307,652 males, 123,299 females) aged 20-39 years were selected based on their ages in 1992 and 1993. Among them, the smoking rate in women was extremely low (0.2%), and they were excluded.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this special issue, Zubak et al [21] examined the effects of scholastic factors-for example, grade point averages, school and other unexcused absences and poor behavior-in relation to illicit drug misuse (IDM) and its initiation among adolescents in Bosnia and Herzegovina. Jee et al [22] investigated the trajectories of different smoking groups of young South Korean male adults and the implication of the habit in their atherosclerotic cardiovascular disease (ASCVD) in middle age. However, substance takers are never restricted to any specific social groups; they can be found in communities of professionals, social talents, elders and university students.…”
Section: Substance Abuse and Different Social Groupsmentioning
confidence: 99%